DEVELOPMENT OF HEATING AND PRODUCTION BOILER PLANT WITH INCREASED RELIABILITY AND ECONOMY - Глущенко, Олена; Назаренко, Владислав (SWorldJournal, 2023)
The work gives an example of the development of a heating and production boiler room for heat supply of production and domestic consumers. As a result of the calculations, the following thermal indicators of the operation of the heating and production boi